Comparative analysis of mesenchymal stem cell and embryonic tendon progenitor cell response to embryonic tendon biochemical and mechanical factors. - Brown, Jeffrey P.; Galassi, Thomas V.; Stoppato, Matteo.; Schiele, Nathan R.; Kuo, Catherine K. (2016)
Introduction: Advances in tendon engineering with mesenchymal stem cells (MSCs) are hindered by a need for cues to direct tenogenesis, and markers to assess tenogenic state. We examined the effects of factors involved in embryonic tendon development on adult MSCs, and compared MSC responses to that of embryonic tendon progenitor cells (TPCs), a model system of tenogenically differentiating cells.; Keywords: basal medium, collagen type I, day, embryonic day, elastin, fetal bovine serum, fibroblast growth factor, green fluorescent protein, growth medium, mesenchymal stem cell, phosphate-buffered saline, quantitative polymerase chain reaction, scleraxis, transforming growth factor, tenomodulin, tendon progenitor cell.; Springer Open.